Mutual Fund Bets on Market Power - Stefan Jaspersen (University of Cologne, Centre for Financial Research (CFR), 2021)
Taking a firm's competitive position into account benefits investors who are better at evaluating this qualitative information. I find that fund managers who overweight companies with market power outperform their peers. Placebo exercises and an exogenous shock to product market competition around the 9/11 terrorist attacks support this finding. Managers with larger bets on market power are more experienced and long-term oriented. They pursue more illiquid investment strategies, select superior innovators, and more actively avoid competition within their portfolio. My findings show how managers with a superior information production utilize hard-to-process information about industrial organization when picking stocks.
Keywords: G11; G12; G14; G23; L11; 330; Mutual fund performance; Information production; Qualitative information; Product market competition